What Should the Aim of Historical Work Be? Ankersmit’s View of Historiography - Zeleňák, Eugen (Dějiny – teorie – kritika, 2008)
Frank Ankersmit’s view of historical work, as outlined mainly in his Narrative Logic (1983), has received considerable attention from philosophers of history and historians. Ankersmit’s narrativism poses interesting questions and casts doubt on some traditional presuppositions of historiography. Th e most surprising and, for some authors, the most appalling is the claim that historical narrative – narratio – cannot have any truth-value. Th is article presents and analyzes three arguments for this claim, which may be found in his Narrative Logic. Moreover, it discusses Ankermist’s alternative criterion for the assessment of historical work. Finally, it presents a criticism of the view that narratio cannot have any truth-value, and identifi es the mistaken assumption in Ankersmit’s argumentation.